Design and Development of Self Check: A Mobile Application for Digital Gadgets Addiction and Countermeasures - Zakaria, Nur Haryani; Tian, Kit Yan; Mat Aji, Zahurin; Katuk, Norliza; Omar, Mazni; Abd Manaf, Abdul Razak (Multidisciplinary Applied Research and Innovation, 2023)
Digital gadgets bring a lot of convenience to humans. Unfortunately, with the uncontrolled usage of digital gadgets, more individuals are becoming addicted to it. Being digitally addicted will bring a lot of harmful effects to a specific individual, both physically and mentally. The current addiction diagnosis applications are mostly web-based making it difficult for individuals to track their test history. This project aims to assist individuals who suspect themselves of having symptoms that are prone to fall for digital gadgets addiction – suggesting appropriate countermeasures before becoming too late. A mobile-application known as SELF CHECK was developed based on the user requirements. An evaluation was carried out to test the user satisfaction and convenience of usage with the developed mobile application. The findings showed that most of the participants were satisfied with the mobile application. The study contributes to a better understanding of the system requirements and user interface of a mobile application for digital gadget addiction, as well as a model for developers and researchers to create similar applications or improve the existing applications.